Proceedings of RFI Mitigation Workshop — PoS(RFI2010) 2010
DOI: 10.22323/1.107.0036
|View full text |Cite
|
Sign up to set email alerts
|

Post-correlation RFI detection

Abstract: Radio astronomy is entering a new era with new and future radio observatories such as the Low Frequency Array and the Square Kilometer Array. We describe in detail an automated flagging pipeline and evaluate its performance. With only a fraction of the computational cost of correlation and its use of the previously introduced SumThreshold method, it is found to be both fast and unrivalled in its high accuracy. The LOFAR radio environment is analysed with the help of this pipeline. The high time and spectral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
167
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(169 citation statements)
references
References 15 publications
2
167
0
Order By: Relevance
“…To summarize, the data were calibrated for the antenna position offsets, elevation dependent gains, global delay, cross-hand delay, bandpass, polarization leakage and angles, and temporal gain variations using the primary and secondary calibrator sources. RFI was identified and flagged with the AOFlagger (Offringa et al 2010). The calibration solutions from the primary and secondary calibrator sources were applied to the target field and several rounds of self-calibration were carried out to refine the gain solutions.…”
Section: Jvla Observationsmentioning
confidence: 99%
“…To summarize, the data were calibrated for the antenna position offsets, elevation dependent gains, global delay, cross-hand delay, bandpass, polarization leakage and angles, and temporal gain variations using the primary and secondary calibrator sources. RFI was identified and flagged with the AOFlagger (Offringa et al 2010). The calibration solutions from the primary and secondary calibrator sources were applied to the target field and several rounds of self-calibration were carried out to refine the gain solutions.…”
Section: Jvla Observationsmentioning
confidence: 99%
“…Flagging for RFI is performed in a standard and automatic fashion using the AOFlagger (Offringa et al 2010). This program has been shown to provide excellent RFI excision with minimal false positives.…”
Section: Pre-processing Stepsmentioning
confidence: 99%
“…This program has been shown to provide excellent RFI excision with minimal false positives. Details of the typical performance of the implemented algorithm on LOFAR data, along with representative RFI statistics, are presented by Offringa et al (2013).…”
Section: Pre-processing Stepsmentioning
confidence: 99%
“…Because of the major increase in resolution and bandwidth of observatories, leading to observations of tens of terabytes, manual data flagging is no longer feasible. Automated RFI flagging pipelines can solve this problem (Flöer et al 2010;Offringa et al 2010b). Alternative RFI strategies might be required for the detection of transients (Ryabov et al 2004;Kocz et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, new algorithms and a pipeline have been implemented to automatically detect RFI with a high accuracy (Offringa et al 2010a,b). Preliminary results have shown that by using these algorithms, only a few percent of the data is lost due to RFI (Offringa et al 2010b).…”
Section: Introductionmentioning
confidence: 99%